A Case Report on Nevirapine Induced Autoimmune Hemolytic Anemia - Devulapalli, Meghana; Kumar G.V, Narasimha (Journal of Pharmacy Practice and Community Medicine)
Nevirapine is one of the first line agents of the anti-retroviral therapy (ART) used widely in the management of human immunodeficiency virus (HIV) infection and also in acquired immunodeficiency syndrome (AIDS). Anemia is often reported in the individuals taking ART. We report a case of Nevirapine induced autoimmune haemolytic anemia (AIHA). This case report creates awareness on the hematologic abnormality caused by the drug requiring immediate medical attention.
Keywords: Drug induced blood disorder; Drug rash; Altered hematology and Quality of life